Magnitude, trends and prevention of road traffic accidents in the Republic of South Africa - Adeloye A. Adeniji; Langalibalele H. Mabuza; Elton Titus (South African Family Practice)
Road traffic injuries (RTIs) constitute one of the five major disease burdens in South Africa with high mortality and morbidity. Thus far, the scientific enquiry into this burden has not been accompanied by successful government efforts to meet the challenge. Currently, more than 1.2 million people die and 20–50 million are with disabilities annually country-wide from RTIs. While there is a progressive reduction in mortality related to human immunodeficiency virus (HIV) conditions as a result of interventions, the mortality from RTI is seen to be progressively worsening as a result of increasing motorisation. There are disparities in the burden of RTI across different countries, with low- and middle-income countries bearing the highest burden. In Africa, 24.1 per 100 000 people die annually from RTI compared to 10.3 per 100 000 people in European countries. This opinion article investigates the magnitude, trends and prevention of RTI in South Africa.